1,2-Diazaazulene und 1,2-Diazapentalene, zwei neue Klassen von nichtbenzoiden Heteroaromaten - Wilhelm Treibs (CHIMIA)
1,2-diazaazulenes and 1,2-diazapentalenes are produced from the corresponding pyrazoles by mild dehydrogenation. They are stable, but sensible against strong acids. They are easily converted in nitrocompounds.